The Human Moment: Self, Other and Suspension in John Banville's Ghosts - McNamee, Brendan (Miscelánea: A Journal of English and American Studies, 2005)
The protagonist of Ghosts is a man isolated from the world around him, and from his own sense of self, by guilt for the crime of murder, but he is imbued also with a fascination for painting –one painting in particular– that seems occasionally to offer release from this condition. Examining how these two elements are intertwined in the novel, this reading suggests that ethics and imagination may be inseparable, and that both may be intrinsic, perhaps even anterior, to the kind of self that the protagonist here longs for –a self that belongs integrally to the world and feels the reality of otherness. The content of the novel, it is argued, is reflected in the form in a way that allows this theme to be enacted. Exploring the ways in which painting versus narrative can be seen as analogous to imagination versus time, the argument is made that the tension between the two is resolved through the idea of anticipation, of suspension, and that this serves both as a basis for art and as a tentative bridge between the reality the protagonist lives in and the one he longs for.
Keywords: Self; Other; Suspension; Ethics; Imagination